Perlindungan Hukum Bagi Konsumen Atas Cacat Produk - Imelda Prisella Ramadhani; Nur Suci Amelia; Ali Munib (International Forum of Researchers and Lecturers, 2026)
Legal protection for consumers against defective products is a crucial issue in the development of modern trade, particularly due to the imbalance of power between business actors and consumers in accessing information and ensuring product safety. This study aims to analyze the forms of preventive and repressive legal protection afforded to consumers, as well as to formulate the responsibilities of business actors for losses arising from defective products under applicable laws and regulations. The research employs a normative juridical method with statutory and conceptual approaches, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that the Consumer Protection Act, the Trade Law, Government Regulation No. 29/2021, and other sectoral regulations provide a strong legal foundation for consumer protection, including information obligations, product safety standards, product recall mechanisms, and the imposition of civil, administrative, and criminal liability on business actors. Furthermore, the principles of strict liability and corporate accountability strengthen the consumer’s position in claiming compensation. In conclusion, Indonesia’s consumer protection system is comprehensively regulated, yet requires more effective supervision to ensure business compliance and enhance consumer safety.